Unraveling customer satisfaction and loyalty at university pool: The impact of marketing mix and service quality - Hariyanto, Tri; Sumaryanto, Sumaryanto; Nasrulloh, Ahmad; Antoni, Muhammad Sigit (Jurnal Keolahragaan, 2024)
Not a few universities currently also act as public services which also provide services to the community, including swimming pool services. This study aims to determine the effect of marketing mix and service quality on customer satisfaction and customer loyalty. The research method used is associative research with a quantitative approach. The subjects of this study were customers in the Universitas Negeri Yogyakarta (UNY) swimming pool of with 102 respondents. Sampling using purpossive sampling technique. Data collection using the survey method using an instrument in the form of a questionnaire. The object of research is marketing mix, service quality, customer satisfaction, and customer loyalty. Data analysis using Structural Equation Model (SEM) analysis techniques with the help of AMOS 22 software. Quantitative descriptive data analysis techniques using SEM assumption tests to analyse the effect of several variables on other variables simultaneously. The results showed that the hypotheses formulated in this study consisted of 4 hypotheses and all were proven to have an effect. The results obtained show that marketing mix affects customer satisfaction, service quality affects customer satisfaction, marketing mix affects customer loyalty, and service quality affects customer loyalty of UNY swimming pool. The research results are proven by the probability value (P values) <0.05. Therefore, it can be concluded that the research hypothesis is proven to be significantly accepted by this research data based on the results of SEM analysis using the AMOS version 22 software.